Square-pulse shearography inspections of metallic parts repaired with a glass fiber reinforced polymer using pressure, radiation, vibration, and induction loading methods. (November 2020) - Oliveira, B.C.F.; Seibert, A.A.; Staub, D.; Albertazzi, A.
Abstract: The use of composites in industrial contexts is already established in recent years. In chemical and oil industries, one application of composite materials is to patch up metallic pipelines and pressure vessels with damages, increasing their lifespans. The damage extension after the repair procedure can be monitored using shearography combined with a loading method such as pressure (PLM), vibration (VLM), induction (ILM), and radiation (RLM). Since the choice of loading method depends on the application, this work proposes a theoretical and practical comparison of PLM, VLM, ILM, and RLM to unveil abnormalities in composite path-up repairs in damaged metallic parts using square-pulse shearography. The results indicate that PLM is the best method, with the lowest number of artifacts. VLM also provided good results and it is more feasible to employ than PLM. These results are important since they indicated more interesting loading procedures to be used with shearography in non-destructive testing techniques. Graphical abstract: Highlights: A comparison between loading methods used with square-pulse shearography is proposed. Pressure, vibration, induction, and radiation loading methods were employed. Metallic samples with GFRP patches and artificial defects were inspected. Results showed that pressure and vibration were the more accurate loading methods.